DEVELOPMENT OF A MODEL FOR THE VARIABLE TENSILE STRESS IN BAND-SAW BLADE (Innovation in Woodworking Industry and Engineering design, 2026)
As a continuation from a previous paper, an original model is proposed for the variable tensile stress in the blade (the saw band) which girdles the two wheels of a band-saw. The case of a spring mechanisms for tensioning the saw band is treated. The internally statically indeterminate problem of the closed band’s contour is solved in a way as required by the course of Strength of Materials. At an instant position of the blade, the tensile stress in all the cross-sections along the band is searched for, taking into account: the assembly pre-tension; the cutting force; the bending of the saw band at the wheel periphery; the heating; the centrifugal inertial forces due to the curvilinear blade’s motion as a new point in the development of the model proposed now. Another new, basic point is that the spring is not ideally stiff but “normal” now. An equation for the tensile internal force at an „opening“ in the band is deduced by involving differential and integral analysis. The equation is solvable by iteration. In case of zero cutting force, the L'Hôpital's rule is applied.